Illicit drugs in wastewater tratment plants: occurrence and behaviour - Viviani, Gaspare; Maida, Carmelo Massimo; Piscionieri, Donatella; Di Gaudio, Francesca; Cosenza, Alida (Italian journal of engineering geology and environment, 2018)
<span data-sheets-value=""1":2,"2":"The occurrence of illicit drugs and related metabolites in two wastewater treatment plants (WWTPs) (namely, WWTP-1 and WWTP-2) located in Sicily (island in the South of Italy) is here discussed. The following illicit drugs have been investigated: methamphetamine, cocaine (COC), 3,4-methylenedioxymethamphetamine (MDMA), methadone (METH), 2-ethylidene-1,5-dimethyl-3,3-diphenylpyrrolidine (EDDP), 3,4-methylenedioxy amphetamine (MDA); 3,4-methylenedioxy ethylamphetamine (MDEA), 11-nor-9-carboxy-Δ9-tetrahydrocannabinol (THC-COOH) and Benzoylecgonine (BEG). BEG, COC, MOR and THC-COOH have the highest concentration for both WWTPs. Inside WWTP-1 negative removal efficiencies were sometimes obtained. For WWTP-2 found for BEG (77.85%), COC (92.34%), CODEINE (64.75%), MOR (90.16%) and THC-COOH (68.64%)."" data-sheets-userformat=""2":13057,"3":"1":0,"11":0,"12":0,"15":"Arial","16":10">The occurrence of illicit drugs and related metabolites in two wastewater treatment plants (WWTPs) (namely, WWTP-1 and WWTP-2) located in Sicily (island in the South of Italy) is here discussed. The following illicit drugs have been investigated: methamphetamine, cocaine (COC), 3,4-methylenedioxymethamphetamine (MDMA), methadone (METH), 2-ethylidene-1,5-dimethyl-3,3-diphenylpyrrolidine (EDDP), 3,4-methylenedioxy amphetamine (MDA); 3,4-methylenedioxy ethylamphetamine (MDEA), 11-nor-9-carboxy-Δ9-tetrahydrocannabinol (THC-COOH) and Benzoylecgonine (BEG). BEG, COC, MOR and THC-COOH have the highest concentration for both WWTPs. Inside WWTP-1 negative removal efficiencies were sometimes obtained. For WWTP-2 found for BEG (77.85%), COC (92.34%), CODEINE (64.75%), MOR (90.16%) and THC-COOH (68.64%).